The consequences of women’s employment: Social, psychological and economic aspects between Sharia guidelines and the reality of positivity and claims of negativity - Khezzari, Saber (The International tax journal, 2025)
Work brings dignity, honour and virtue; it combats boredom and idleness, and prevents excessive talk. It is required of both men and women equally. As social theorists have said, ‘If you want to destroy someone, leave them without work.’ God despises the idle servant because He loves to see His servants proving themselves, being productive and benefiting themselves and their society. He dislikes laziness and neglecting life’s obligations. The era of developments and new demands has brought many new issues and problems to families and communities that were not previously addressed. One of the most important and prominent issues is women’s employment, which has become a hot topic with everyone having their own view on it. Conferences, seminars, lectures and publications have been organised to study this phenomenon, mitigate its risks, regulate it and eliminate its negative aspects. Our research is a small contribution and an attempt to propose some solutions that may be accepted and considered.